2021
DOI: 10.1186/s12903-021-01530-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of single implant supported crowns versus 3-unit implant-supported fixed dental prostheses in Dubai Health Authority: a retrospective study

Abstract: Background This study assessed retrospectively the clinical outcomes of single implant-supported crowns and implant-supported fixed dental prostheses (FDPs). Methods This case series compared biological and technical complications in single implant-supported crowns and implant-supported bridges in a time framed sample of all patients who received dental implants between 2009 and 2016 in Dubai Health Authority. Only 3-unit implant-supported prosthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 41 publications
0
11
1
Order By: Relevance
“…The findings of the present study were not consistent with that of Alhammadi et al 20 who reported implants supporting 3-unit fixed bridge showed greater marginal bone loss and more frequent technical complications than single implants. This difference may be attributed to the fact that variables such as diameters or lengths of the implant were not included in their study although they included not only posterior but also anterior implant fixed restorations.…”
Section: Discussioncontrasting
confidence: 99%
“…The findings of the present study were not consistent with that of Alhammadi et al 20 who reported implants supporting 3-unit fixed bridge showed greater marginal bone loss and more frequent technical complications than single implants. This difference may be attributed to the fact that variables such as diameters or lengths of the implant were not included in their study although they included not only posterior but also anterior implant fixed restorations.…”
Section: Discussioncontrasting
confidence: 99%
“…A retrospective study to compare 3 different types of implant-supported fixed dental prostheses—3 non-splinted crowns, 3 splinted crowns, and 3-unit implant-supported bridges over 2 implants—reported that the peri-implantitis incidence rate of 3-unit implant-supported bridges was comparable to that of non-splinted crowns, and that it was lower than that of splinted crowns [ 32 ]. In contrast, Alhammadi et al [ 33 ] found that the marginal bone loss around 3-unit implant-supported fixed prostheses was significantly greater than that around single crown-supported implants 1 year after prosthetic loading. In the present study, implant-supported bridges had greater marginal bone loss than single or splinted crowns, which is in accord with the findings of Alhammadi et al [ 33 ].…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, Alhammadi et al [ 33 ] found that the marginal bone loss around 3-unit implant-supported fixed prostheses was significantly greater than that around single crown-supported implants 1 year after prosthetic loading. In the present study, implant-supported bridges had greater marginal bone loss than single or splinted crowns, which is in accord with the findings of Alhammadi et al [ 33 ]. Although the prosthetic types were divided into 3 groups in this study, the situation for each prosthetic type varied more than could be captured by a tripartite classification.…”
Section: Discussionmentioning
confidence: 97%
“…Relating this to the clinical results obtained, it seems that the numerical experiments did not take into account the role of technical fabrication difficulties (risk of residual stresses, problems with compensating for nonparallelism) and the role of oral hygiene, which is more difficult in splinted crown work. There are reports [ 46 ] describing bridgeworks as significantly more affected by marginal crestal bone loss compared to single-crown-supported implants in short-term studies. In this long-term study, however, single crowns were the best prosthetic solution.…”
Section: Discussionmentioning
confidence: 99%